Gilbert Simondon: un’assiomatica aperta - Ugazio, Ugo Maria (Philosophy Kitchen - Rivista di filosofia contemporanea, 2016)
Focusing on the Simondon’s conference Forme, information, potentiels, the following analysis will briefly consider the conflicting relation between ontological questions as individuation, pre-individual, transduction, metastability and the question of technological invention.